Failure Mechanism and Stability Control of Surrounding Rock of Docking Roadway under Multiple Dynamic Pressures in Extrathick Coal Seam - Xiangye Wu; Shuai Wang; Chen Tian; Changxing Ji; Jingya Wang (Geofluids)
In view of multiseam mining under goaf, the surrounding rock control problem of lower coal roadway will be affected by concentrated coal pillar left in upper coal seam goaf and dynamic pressure superposition of working face in this coal seam. Under the geological environment of No. 16 extrathick coal seam in the Laoshidan coal mine and taking the working face 031604 as the research background, the reasonable docking position selection of the withdrawal roadway and the docking roadway in the middle mining period and the surrounding rock stability control problems of the withdrawal roadway and the docking roadway during the final mining period were studied by using the methods of field theoretical analysis, numerical simulation, and field measurement. The mechanical mechanism of the nonuniform failure of the retreating roadway and the docking roadway during the final mining period is shown, and the control method of the surrounding rock stability of the roadway is put forward and applied. The results show that (1) through the analysis of the superimposed stress under the concentrated coal pillar and the coal seam in advance, the specific butt joint position is arranged at 860 m away from the open-off cut, which is 10 m away from the goaf of No. 12 coal seam. (2) With the working face 031604 advancing through the process, the deviatoric stress value of the withdrawal roadway gradually increases, the maximum principal stress of the two sides of the roadway deflects clockwise from the vertical direction to the horizontal direction, its angle also gradually increases, and the shape of the plastic zone gradually expands from symmetry to asymmetry. (3) It is revealed that the peak value of deviatoric stress on both sides of the docking position of docking roadway increases gradually under the influence of mining and deflects anticlockwise to the vertical direction with the principal stress angle. The joint action of both is the mechanical mechanism that causes the plastic zone to expand in an asymmetric shape. (4) The coordinated control scheme of support (anchor bolt and anchor cable)—modified (grouting)—is adopted for the withdrawal roadway, and the coordinated control scheme of support (anchor bolt and anchor cable)—changing the cross-section shape of the roadway—is adopted for the docking roadway. The purpose of the smooth connection of working face and rapid and safe withdrawal of equipment is achieved on site.